2016
DOI: 10.1038/srep39744
|View full text |Cite
|
Sign up to set email alerts
|

The levels of the sex hormones are not different between type 1 and type 2 endometrial cancer

Abstract: The involvement of hormonal factors in developing endometrial cancer is well documented. In particular, excess or unopposed estrogen is a major risk factor. Endometrial cancer is divided into estrogen-dependent and estrogen-independent types. Studies suggested that the subtypes of endometrial cancer share many common risk factors. Whether the levels of sex hormones differ between types 1 and 2 endometrial cancer has not been investigated. In this study, levels of estrogen, progesterone, testosterone, follicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The difference in the incidence of endometrial and ovarian cancers may result in differences in clinical characteristics and pathological parameters by ethnicities. Our previous studies reported that endometrial and ovarian cancers occur more frequently in Chinese women before menopause [22][23][24], whilst 75% of endometrial and ovarian cancers occur after menopause in Caucasians [25]. Our recent unpublished data also showed differences in clinical characteristics and pathological parameters in breast cancer between Chinese and New Zealand Europeans.…”
Section: Ivyspringmentioning
confidence: 67%
“…The difference in the incidence of endometrial and ovarian cancers may result in differences in clinical characteristics and pathological parameters by ethnicities. Our previous studies reported that endometrial and ovarian cancers occur more frequently in Chinese women before menopause [22][23][24], whilst 75% of endometrial and ovarian cancers occur after menopause in Caucasians [25]. Our recent unpublished data also showed differences in clinical characteristics and pathological parameters in breast cancer between Chinese and New Zealand Europeans.…”
Section: Ivyspringmentioning
confidence: 67%
“…Recent studies have shown that both type I and type II endometrial cancers share several risk factors (Setiawan et al, 2013), and patients with these cancers show no difference in E2 and progesterone blood levels, which suggest similar pathogenesis (Wan et al, 2016). Obesity is an important risk factor for the development of endometrial cancer.…”
Section: Hormone-dependent Cancersmentioning
confidence: 99%
“…Epidemiological studies have identified several risk factors for the development of endometrial cancer, which include obesity (Jenabi and Poorolajal, 2015 ), estrogen-only therapy, early menarche, late menopause, and nulliparity, among others. Recent studies have shown that both type I and type II endometrial cancers share several risk factors (Setiawan et al, 2013 ), and patients with these cancers show no difference in E2 and progesterone blood levels, which suggest similar pathogenesis (Wan et al, 2016 ). Obesity is an important risk factor for the development of endometrial cancer.…”
Section: Hormone-dependent Cancersmentioning
confidence: 99%
“…11 In addition to decreasing oestrogen levels to inhibit the progression of EC, some reports have suggested that high levels of LH and FSH stimulate EC cell growth in vitro, and GnRH-as may inhibit pathogenesis by suppressing gonadotrophin levels. 12 Furthermore, the autocrine LHRH regulatory system is likely present in some human malignant tumours, such as breast, ovary, endometrium, and prostate cancer. 11 Evidences have been proven that GnRH-as have direct antitumour effects on endometrial cancer.…”
Section: The Mechanism Of Action and Clinical Use Of Gnrh-asmentioning
confidence: 99%